Psychological Features Of The Development Of Thinking Skills In Children Aged 5-6 Years Old - Kholmatova Gulyora Obidovna (Periodica Journal, 2024)
This article describes the pedagogical and psychological features of the development of thinking skills in children 5-6 years old. The article reflects the problems of forming the concept of thinking, thinking abilities and thinking ability in children 5-6 years old, and also provides recommendations based on the author’s comments.
Keywords: thinking ability; development of thinking ability; free-thinking